Urethral Duplication with a Cystic Phallic Urethra Associated with a Uterus Didelphys, Partial Agenesis of the Tibia, and an Equinovarus Foot - Edwige Kafando; Boniface Moifo; Landry Mbouche; Derek Ndangoh; Evelyn Mah; Faustin Mouafo Tambo (Case Reports in Radiology)
Urethral duplication is a rare congenital malformation, especially in females. It may be associated with complex urogenital malformations, but the association with a cystic phallic urethra and a uterus didelphys is exceptional. We report a case of a newborn with urethral duplication, with the accessory urethra exteriorized by a large cyst, associated with a uterus didelphys and bone malformations. We discuss the clinical, radiographic, and therapeutic aspects as well as a literature review.